Does Gender Inequality Hinder Development and Economic Growth? Evidence and Policy Implications - Bandiera, Oriana; Natraj, Ashwini (Oxford University Press on behalf of the World Bank, 2014)
Does the existing evidence support policies that foster growth by reducing gender inequality? We argue that the evidence based on differences across countries is of limited use for policy design because it does not identify the causal link from inequality to growth. This, however does not imply that inequality-reducing policies are ineffective. In other words, the lack of evidence of a causal link is not in itself evidence that the causal link does not exist. Detailed micro studies that shed light on the mechanisms through which gender inequality affects development and growth are needed to inform the design of effective policies.